從教師專業發展評鑑探究國中教師專業學習社群之成效：以高雄市為例 A Study of the Effectiveness of Teacher Professional Learning Communities from the Perspective of Teacher Evaluation for Professional Development: A Case Study of Kaohsiung City Junior High Schools - 馮莉雅 Feng, Li-Yia (National Changhua University of Education, 2013)
本研究以高雄市國中參與專業學習社群的教師為研究對象，探討國中教師專業學習社群的運作成效與其相關問題。本研究採用問卷調查法和訪談法，以高雄市參與教師專業學習社群的141 位國中教師為研究對象，採用次數分配、獨立樣本t 檢定、相依樣本t 檢定、單因子變異數分析、逐步多元迴歸等統計方法。研究結論如下： （一）高雄市國中大多數教師專業學習社群運作情形良好，教師有高度的繼續參與意願，能提升教師的專業知能，研習方式多元，教學觀察是有效的社群活動，但校內計畫整合情形不佳。（二）高雄市國中教師對專業學習社群成效有中高的認同度。（三）社群的運作次數、社群規模、教師專業發展評鑑的學校計畫類型或研習情形，會影響教師對專業學習社群運作成效之看法。 A questionnaire survey approach and an interview were employed in the study. A selective random sample of 141 teachers from 18 junior high schools was drawn in Kaohsiung City. Frequency distribution, Independent-Sample t Test, and One-Way ANOVA were used to examine the questions. The conclusions are as follows: 1.Junior high school teachers viewed "support relation", "collective inquiry and shared personal practice", and "shared vision and value" as the most important characteristics base for the development of teacher professional learning communities. 2.Junior high school teachers in Kaohsiung city have medium-high agreement in the effectiveness of professional learning communities. 3.The frequency of the communities, size, and projects, seminars of teacher evaluation for professional development influence teachers' ideas about the performance of professional learning communities.